Copper as the most likely pathogenic divergence factor between lung fibrosis and emphysema. (November 2018) - Janssen, Rob; de Brouwer, Bart; von der Thüsen, Jan H.; Wouters, Emiel F.M.
Abstract: Although fibrosis and emphysema are in many ways on opposite ends of the pulmonary parenchymal disease spectrum, they seem to share common pathomechanistic steps. This is illustrated by the coexistence of both entities in lungs of individuals with combined pulmonary fibrosis and emphysema. Macroproteins elastin and collagen are major constituents of the pulmonary extracellular matrix. The prevailing paradigm states that emphysema is caused by an imbalance between destructive proteolytic and protective antiproteolytic enzymes leading to accelerated degradation of elastin fibers in the lungs. Rates of elastin breakdown, however, are equally enhanced in patients with idiopathic pulmonary fibrosis (IPF) and emphysema. Excessive accumulation of collagen is a hallmark of IPF. Surprisingly, collagen levels in the lung parenchyma of patients with emphysema are also higher than in controls. The concentration of elastin fibers is elevated in fibrotic lungs, despite accelerated elastinolysis, suggesting that elastin repair is also enhanced in IPF. Since elastin concentrations are reduced in emphysematous lungs, the factor of divergence between emphysema and fibrosis seems to be the degree of elastin repair. Multiple elastin repair steps can be deduced of which tropoelastin synthesis and crosslinking of tropoelastin polymers by the copper dependent enzyme lysyl oxidase seem to be the most important ones. We suspect that the distinction in the pathogeneses of lung fibrosis and emphysema depends on the local availability of copper to activate sufficient lysyl oxidase for elastin crosslinking, and suggest assessing the effects of inhalation therapy with copper plus heparin in emphysema and heparin monotherapy in IPF.